Given that men and women are equal we can say that:
(masculine variable + femboys) = (tomboys + feminine variable)
We can now simplify by removing boys from both ends of the equasion
(masculine variable + fem) = (tom + feminine variables)
We'll need a fem and tom on each side to balance the equasion, so
((tom + masculine suffix) + fem) = (tom + (fem + feminine suffix))
We can simplify this again and get
masculine suffix = feminine suffix.
Therefore we can only conclude that masculine guys are called tomgirls and feminine girls are called femgirls.